If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-4 + 4x)(x + -3) = 0 Reorder the terms: (-4 + 4x)(-3 + x) = 0 Multiply (-4 + 4x) * (-3 + x) (-4(-3 + x) + 4x * (-3 + x)) = 0 ((-3 * -4 + x * -4) + 4x * (-3 + x)) = 0 ((12 + -4x) + 4x * (-3 + x)) = 0 (12 + -4x + (-3 * 4x + x * 4x)) = 0 (12 + -4x + (-12x + 4x2)) = 0 Combine like terms: -4x + -12x = -16x (12 + -16x + 4x2) = 0 Solving 12 + -16x + 4x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(3 + -4x + x2) = 0 Factor a trinomial. 4((1 + -1x)(3 + -1x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {1, 3}
| x^4+44x^2-2880=0 | | (x-2+i)(x-2-i)= | | 0.4(2-9)=0.2(q+7) | | -5(b+6)-2=-11-8b | | 5-2+3x=17+12x-23 | | 2(1+2)=1(2+3x) | | 5(6x-8)=10+5x | | 3-5(-7+x)=-32+5x | | 5(6x-8)=10 | | -13=-(-7+b) | | 0.15x+0.05(12-x)=0.10(-10) | | -4(v+5)=-25-5v | | 6(1+6n)+6=5(6n+2)+8n | | 1000*y=2.7963 | | -28+8m=-6(6-2m)-4 | | j^2-8= | | W^2+5w-44=0 | | 4.2*y=39.06 | | -3(1-6m)+6=3(m+1) | | n=3n-f | | 8n+33=-7(n+6) | | 0.5x-2.5=3.9x+2.4 | | (x^3-5x^2+12x+18)(x-2)= | | 28+3p=-1-7(5-5p) | | 28-0.03y=0.07y-12 | | -(r-7)+1=14-3r | | 5x+20=250 | | 5n-4=-19 | | -8(3x+7)=28+4x | | 5+7(7-8a)=390 | | 15=(2t-1) | | f(x)=(x-5)(x+6)(x+2) |